2016
DOI: 10.1097/grf.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Occult Uterine Sarcoma in Presumed Uterine Fibroids

Abstract: Symptomatic fibroids are a common indication for hysterectomy or myomectomy. Although rare, unexpected gynecologic malignancies in presumed fibroids have been documented. In cases where tissue retrieval is performed through morcellation, there is increasing concern that intra-abdominal dispersion of occult uterine malignancies may lead to peritoneal dissemination and worse outcomes. We examined the available literature to determine the prevalence of all uterine cancers in women undergoing hysterectomy or myome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…The incidence of post-operatively diagnosed sarcomas (LMS and endometrial stromal sarcoma) has been estimated to be between 1:350 to 1.4:500 in patients undergoing hysterectomies or myomectomies (Park et al, 2011, Lissoni et al, 1998, Food and Drug Administration, 2014, Kamikabeya et al, 2010). The largest single institution series showed the incidence of sarcomas to be 20:4785 patients (Cui and Wright, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of post-operatively diagnosed sarcomas (LMS and endometrial stromal sarcoma) has been estimated to be between 1:350 to 1.4:500 in patients undergoing hysterectomies or myomectomies (Park et al, 2011, Lissoni et al, 1998, Food and Drug Administration, 2014, Kamikabeya et al, 2010). The largest single institution series showed the incidence of sarcomas to be 20:4785 patients (Cui and Wright, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In laparoscopy, the possibility of facing a uterine sarcoma (leiomyosarcoma followed by endometrial stromal sarcoma and carcinosarcoma) misdiagnosed as myoma exists, with a prevalence that ranges from 0.00% to 0.49% [ 80 ], although the risk has been probably overestimated [ 21 ]. To eliminate the risk of inadvertent tissue spread during surgery, “in bag” myoma excision and morcellation have been proposed to avoid ethical and medicolegal issues in case of unexpected malignancy [ 81 83 ].…”
Section: Uterine Myomasmentioning
confidence: 99%
“…Among them, 34 cases (28%) incurred uterus morcellation, which may increase the risk of postoperative metastasis within three months. Recently, other studies also showed that laparoscopic surgery may lead to malignant planting in operating hole, abdominal and pelvic sarcoma 11 49 51 52 53 .…”
Section: Uterus Morcellation and Metastasis Of Uterine Sarcomamentioning
confidence: 99%